Repeatable glucocorticoid expression is associated with behavioural syndromes in males but not females in a wild primate. Issue 9 (4th September 2019) - Tkaczynski, P. J.; Ross, C.; Lehmann, J.; Mouna, M.; Majolo, B.; MacLarnon, A.
Abstract : Behavioural syndromes are a well-established phenomenon in human and non-human animal behavioural ecology. However, the mechanisms that lead to correlations among behaviours and individual consistency in their expression at the apparent expense of behavioural plasticity remain unclear. The 'state-dependent' hypothesis posits that inter-individual variation in behaviour arises from inter-individual variation in state and that the relative stability of these states within an individual leads to consistency of behaviour. The endocrine stress response, in part mediated by glucocorticoids (GCs), is a proposed behavioural syndrome-associated state as GC levels are linked to an individual's behavioural responses to stressors. In this study, in wild Barbary macaques ( Macaca sylvanus ), consistent inter-individual differences were observed in both sexes for GC activity (faecal glucocorticoid, fGC concentrations), but not GC variation (coefficient of variation in fGC concentrations). The expression of the behavioural syndrome 'Excitability' (characterized by the frequencies of brief affiliation or aggressive interactions) was related to GC activity in males but not in females; more 'excitable' males had lower GC activity. There was no relationship in females between any of the behavioural syndromes and GC activity, nor in either sex with GC variation. The negative relationship between GC activity and Excitability in males provides some support for GC expression as a behavioural syndrome-generating state under the state-dependent framework. The absence of this relationship in females highlights that state-behavioural syndrome associations may not be generalizable within a species and that broader sex differences in state need to be considered for understanding the emergence and maintenance of behavioural syndromes.